2014
DOI: 10.1371/journal.pone.0089752
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Baicalin on Metabolism of Phenacetin, a Probe of CYP1A2, in Human Liver Microsomes and in Rats

Abstract: Baicalin has been used as mainly bioactive constituent of about 100 kinds of traditional Chinese medicines in Chinese pharmacopoeia. The effect of baicalin on cytochrome P450 should be paid more attention because baicalin was used widely. The aim of this study was to investigate whether baicalin could inhibit CYP1A2 in pooled human liver microsomes (HLMs) and in rats in vivo and the gene polymorphisms could affect inter-individual variation in IC50 in 28 human livers. Phenacetin was used as probe of CYP1A2. Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…This could be due in part to the formation of this active metabolite having multiple pathways and involving multiple enzymes, thereby allowing for numerous opportunities for inhibition in the measured reaction velocities. Gao et al have previously reported that baicalin inhibits human CYP1A2 via mixed type inhibition using phenacetin as a probe [13]. Because CYP1A2 contributes to the formation of DES, which is the one precursor metabolites to ENDO, inhibiting this enzyme would reduce the amount of ENDO formed which is consistent with our data.…”
Section: Metabolic Inhibition By Skullcapsupporting
confidence: 92%
“…This could be due in part to the formation of this active metabolite having multiple pathways and involving multiple enzymes, thereby allowing for numerous opportunities for inhibition in the measured reaction velocities. Gao et al have previously reported that baicalin inhibits human CYP1A2 via mixed type inhibition using phenacetin as a probe [13]. Because CYP1A2 contributes to the formation of DES, which is the one precursor metabolites to ENDO, inhibiting this enzyme would reduce the amount of ENDO formed which is consistent with our data.…”
Section: Metabolic Inhibition By Skullcapsupporting
confidence: 92%
“…We defined ‘smokers’ as those who smoke 11 cigarettes or more smoking per day, ‘non-smokers’ as individuals who had never smoked or smoke less than 11 cigarettes per day. The standard referred the previous method [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Both compounds might not affect other CYPs, including CYP 2E1 and 3A, at the concentrations tested (∼100 μM). These results were consistent with previous reports ( Gao et al ., 2013 ; Gao et al ., 2014 ). Gao et al .…”
Section: Discussionmentioning
confidence: 99%
“…For an example, baicalein significantly increased the CYP3A4 activity in vitro , whereas the pharmacokinetics of certain drugs metabolized by CYP3A4 were inhibitedly altered in the presence of baicalein ( Cho et al ., 2011 ; Li et al ., 2011 ). The effects of baicalin on drug metabolism were also evaluated through in vivo studies ( Gao et al ., 2013 ; Gao et al ., 2014 ). Considering these results, the effects of baicalin and baicalein on CYP isozymes and pharmacokinetics of certain drugs needed to be re-evaluated.…”
Section: Introductionmentioning
confidence: 99%